2020
DOI: 10.1093/ofid/ofaa439.954
|View full text |Cite
|
Sign up to set email alerts
|

764. Correlates of Lost to Follow-up Among Newly Diagnosed Older People with HIV in Ukraine

Abstract: Background Ukraine has the second largest HIV epidemic in Eastern Europe and Central Asia. Older People with HIV (OPWH) are at increased risk of poor outcomes compared to younger patients. We examined the prevalence and correlates of loss to follow-up (LTFU) among newly diagnosed patients in Ukraine. Methods Retrospective chart review was conducted of 400 patients newly diagnosed with HIV July 1, 2017 - Dec 1, 2018. Data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…While no studies in Ukraine have assessed HIV knowledge specifically among older adults, a study conducted in Ukraine among PLWH of all ages identified a lack of knowledge about HIV as a major barrier to linkage to care (Kiriazova et al, 2018). The results of this study, as well as findings globally in other settings showing that OPWH possess low levels of knowledge about HIV (Henderson et al, 2004) and do not perceive themselves to be at risk for HIV (Altschuler et al, 2008;Jackson et al, 2005;Maes & Louis, 2003), suggest that HIV knowledge and risk perception may be lower in Ukrainian OPWH compared with younger patients and may contribute to the low linkage to care seen in Ukraine (Allen et al, 2020b). In general, increased awareness of HIV in older adults and the variety of mechanisms by which HIV is transmitted is needed among the general population, providers, and at the institutional level in Ukraine.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…While no studies in Ukraine have assessed HIV knowledge specifically among older adults, a study conducted in Ukraine among PLWH of all ages identified a lack of knowledge about HIV as a major barrier to linkage to care (Kiriazova et al, 2018). The results of this study, as well as findings globally in other settings showing that OPWH possess low levels of knowledge about HIV (Henderson et al, 2004) and do not perceive themselves to be at risk for HIV (Altschuler et al, 2008;Jackson et al, 2005;Maes & Louis, 2003), suggest that HIV knowledge and risk perception may be lower in Ukrainian OPWH compared with younger patients and may contribute to the low linkage to care seen in Ukraine (Allen et al, 2020b). In general, increased awareness of HIV in older adults and the variety of mechanisms by which HIV is transmitted is needed among the general population, providers, and at the institutional level in Ukraine.…”
Section: Discussionsupporting
confidence: 50%
“…In Ukraine, 15% of new HIV diagnoses occur in people over the age of 50, and this percentage is increasing (Rozanova, 2018). Our ongoing research has also shown that OPWH in Ukraine experience delays in antiretroviral therapy (ART) initiation and are over 3 times more likely to be lost to follow-up compared with younger patients (Allen et al, 2020a(Allen et al, , 2020b. Despite these figures, there are a lack of targeted prevention or treatment programs for OPWH in Ukraine.…”
Section: Older People With Hiv (Opwh) In Ukrainementioning
confidence: 99%
See 1 more Smart Citation
“…However, the vast majority of OPWH, including those with an addiction history, reported low levels of alcohol use, which is consistent with other studies, despite earlier hypotheses that lockdown will result in higher alcohol use [ 8 ]. It is possible that social support (including by trusted clinicians) to vulnerable OPWH with comorbid addictions has played a significant protective role during the COVID-19 lockdown [ 27 ]. Early findings from other global regions [ 72 ] also suggest that patients with comorbid SUD and HIV who were stably linked to addiction care had no significant changes in risk behaviours during the COVID-19 lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…About a quarter of PWH in Ukraine are OPWH, defined as those aged ≥50 years [ 22 , 23 , 24 , 25 ]. While Ukraine has made significant strides in HIV care for key populations, including people who inject drugs, men who have sex with men, and persons engaged in commercial sex work, OPWH have not been a target priority population [ 26 ], with emerging challenges to the continuity of care during COVID-19 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%